Shared gene characteristics and molecular mechanisms of macrophages M1 polarization in calcified aortic valve disease - Qin, Ming; Chen, Qian; Li, Ning; Xu, Xiangyang; Wang, Chuyi; Wang, Guokun; Xu, Zhiyun (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background： CAVD is a common cardiovascular disease, but currently there is no drug treatment. Therefore, it is urgent to find new and effective drug therapeutic targets. Recent evidence has shown that the infiltration of M1 macrophages increased in the calcified aortic valve tissues, but the mechanism has not been fully elucidated. The purpose of this study was to explore the shared gene characteristics and molecular mechanisms of macrophages M1 polarization in CAVD, in order to provide a theoretical basis for new drugs of CAVD. Methods： The mRNA datasets of CAVD and M1 polarization were downloaded from Gene Expression Omnibus (GEO) database. R language, String, and Cytoscape were used to analyze the functions and pathways of DEGs and feature genes.Immunohistochemical staining and Western Blot were performed to verify the selected hub genes. Results： CCR7 and GZMB were two genes appeared together in hub genes of M1-polarized and CAVD datasets that might be involved in the process of CAVD and macrophages M1 polarization. CCR7 and CD86 were significantly increased, while CD163 was significantly decreased in the calcified aortic valve tissues. The infiltration of M1 macrophages was increased, on the contrary, the infiltration of M2 macrophages was decreased in the calcified aortic valve tissues. Conclusion： This study reveals the shared gene characteristics and molecular mechanisms of CAVD and macrophages M1 polarization. The hub genes and pathways we found may provide new ideas for the mechanisms underlying the occurrence of M1 polarization during CAVD process.